Cadaveric Spinal Surgery Simulation: A Comparison of Cadaver Types. (June 2016) - Tomlinson, James E.; Yiasemidou, Marina; Watts, Anna L.; Roberts, Dave J. H.; Timothy, Jake
Study Design: Single-blinded study. Objective: To assess the suitability of three types of cadaver for simulating pedicle screw insertion and establish if there is an ideal. Methods: Three types of cadaver—Thiel-embalmed, Crosado-embalmed, and formaldehyde-embalmed—were draped and the spines exposed. Experienced surgeons were asked to place pedicle screws in each cadaver and give written questionnaire feedback using a modified Likert scale. Soft tissue and bony properties were assessed, along with the role of simulation in spinal surgery training. Results: The Thiel cadaver rated highest for soft tissue feel and appearance with a median score of 6 for both (range 2 to 7). The Crosado cadaver rated highest for bony feel, with a median score of 6 (range 2 to 7). The formaldehyde cadaver rated lowest for all categories with median scores of 2, 2.5, and 3.5, respectively. All surgeons felt pedicle screw insertion should be learned in a simulated setting using human cadavers. Conclusion: Thiel and Crosado cadavers both offered lifelike simulation of pedicle screw insertion, with each having advantages depending on whether the focus is on soft tissue approach or technical aspects of bony screw insertion. Both cadaver types offer the advantage of long life span, unlike fresh frozen tissue, which means cadavers can be used multiple times, thus reducing the costs.